2009
DOI: 10.1063/1.3074502
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature negative differential resistance in DNA-based molecular devices

Abstract: A molecular device fabricated from metallic deoxyribonucleic acid (M-DNA) exhibits a negative differential resistance (NDR) behavior. When two gold electrodes were connected by Ni2+-chelated DNA, which was converted from λ-DNA, not only was the conductivity of DNA improved, but a NDR device was formed as a full cyclic voltage sweep was applied to measure its current versus voltage characteristics at room temperature and in an ambient environment. Such electronic characteristics of a M-DNA device may have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 21 publications
2
39
0
Order By: Relevance
“…[53][54][55] As a consequence, NDR has been at the focus of a number of recent experimental 56,57 and theoretical [58][59][60] papers. The NDR effect found by Quek et al 58 is explained in terms of gold electrodes supporting molecule-electrode contact-driven NDR, where the coupling to the rather narrow bands of 1-D Au chains stretched on the surface plays an important role.…”
Section: Comments On Ndr Effectsmentioning
confidence: 99%
“…[53][54][55] As a consequence, NDR has been at the focus of a number of recent experimental 56,57 and theoretical [58][59][60] papers. The NDR effect found by Quek et al 58 is explained in terms of gold electrodes supporting molecule-electrode contact-driven NDR, where the coupling to the rather narrow bands of 1-D Au chains stretched on the surface plays an important role.…”
Section: Comments On Ndr Effectsmentioning
confidence: 99%
“…22 Recently, Ni-DNA molecules 50-100 nm in length 22,24 were shown to exhibit a negative differential resistance (NDR) effect at room temperature, a characteristic of memristive devices. 21 This behavior may be attributed to the redox current (I red ) of Ni ions. 24 Both chelated Ni ions and the π-stacking bases in the DNA duplex were found to be essential for charge transport in Ni-DNA nanowires.…”
Section: Introductionmentioning
confidence: 99%
“…21,24 The ratio of redox species of Ni ions (Ni 2+ /Ni 3+ ) can be changed when the external biases exceed the threshold of redox potential of Ni ions, 4 indicating that the Ni-DNA nanowire may exhibit a capacitive effect. In this study, a micrometer-long Ni-DNA nanowire is developed and characterized to explore its potential in the development of nanowire-based electronic devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The electron transport along helical molecules, such as DNA and α-helical protein, has been receiving much attention among the scientific communities [7][8][9][10][11][12][13][14][15][16][17], because this subject can enrich our knowledge regarding the electronic properties of low-dimensional systems due to the unique helix structure and provides valuable information for understanding the biological processes in living organisms [18][19][20]. It was reported by direct charge transport experiments that double-stranded DNA (dsDNA) could exhibit fascinating physical phenomena, such as the proximity-induced superconductivity [21], the negative differential resistance [22], and the piezoelectric effect [23]. Additionally, it was shown that both dsDNA and α-helical protein can behave as electric field-effect transistors [24][25][26][27] and as efficient spin filters [28][29][30][31][32][33][34][35].…”
mentioning
confidence: 99%